MEMAHAMI GANGGUAN BERBICARA CADEL DAN DAMPAKNYA PADA KOMUNIKASI - Desy Wulandari; Meilan Arsanti (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
A lisp is a speech disorder that makes it difficult for a person to pronounce words fluently, especially the "R" sound. Physiological, environmental, psychological or health factors are some of the causes. This research uses a qualitative approach. Researchers will present the results in detail. To help children overcome this disorder, early detection and speech therapy support are essential. The role of family and environment is also important in helping children with lisp grow to communicate. If the lisp problem is serious or persists for a long time, medical intervention may be necessary.